Characterization of Secondary Metabolites and Cytotoxic Assay of Haliclona sp. Sponge Against T47D Breast Cancer Cells - Ajuk Sapar; Millenia Millenia; Anthoni Batahan Aritonang; Rudiyansyah Rudiyansyah; Winda Rahmalia (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Characterization of secondary metabolites and cytotoxic testing of Haliclona sp. against T47D breast cancer cells were conducted in this study. The objective was to assess the cytotoxicity of T47D cancer cells and identify the functional groups involved. The research methods employed included maceration, partitioning, phytochemical testing, toxicity testing using the BSLT method, separation through flash column chromatography (FCC), cytotoxic testing using the MTT method, and characterization using FTIR. The partition results of methanol extract consist of n-hexane, ethyl acetate, and methanol-water fractions. The methanol extract demonstrated high toxicity, with an LC50 of 5.21 ppm. Among the fractions, the ethyl acetate fraction exhibited the highest toxicity compared to the n-hexane and methanol-water fractions, with LC50 values of 25.76 ppm, 42.71 ppm, and 55.26 ppm, respectively. Phytochemical testing of the ethyl acetate fraction yielded positive results for terpenoids, steroids, alkaloids, and phenolic compounds. The ethyl acetate fraction was further separated using flash column chromatography, resulting in ten combined fractions (M1-M10). The cytotoxicity tests of the M3 fraction against 747D breast cancer cells showed non-toxic effects, with an IC50 value of 1382.29 ppm. The FTIR analysis of the M3 fraction revealed the presence of functional groups such as O-H, =C-H, C-H aliphatic, C=O, and C=C, which is indicative of the presence of terpenoids, steroids, and esters.